Pemberdayaan Masyarakat Nelayan Melalui Penguatan Ekonomi Lokal di Kabupaten Aceh Barat - Anggrainie, Syarifah Wirda; Mardhatillah, Muntaha (Journal of Political Sphere, 2024)
The empowerment of fishing communities in West Aceh Regency through local economic strengthening has gained significance, especially amidst the socioeconomic challenges posed by the COVID-19 pandemic. This research highlights the economic vulnerabilities of coastal communities, most of whom belong to the lower-income group, a condition further exacerbated by the pandemic. While government initiatives, such as facilitating fishery export collaborations, have aimed to bolster the local economy, their implementation has been hindered by limited administrative services and insufficient community participation. Findings reveal that financial aid programs during the pandemic were often poorly targeted and ineffective in addressing the core issues faced by fishers. To overcome these challenges, empowerment strategies such as establishing cooperatives, collective business management, and strengthening partnerships with stakeholders are proposed. In Samatiga Sub-district, efforts have been directed toward enhancing the market value of fishery products through organized fisher groups. However, both structural limitations and local government constraints pose challenges to the success of these programs. A holistic, participatory, and sustainable approach is essential for fostering the welfare of fishing communities and achieving robust local economic development in West Aceh Regency.AbstrakPemberdayaan masyarakat nelayan di Kabupaten Aceh Barat melalui penguatan ekonomi lokal menjadi isu yang semakin penting, terutama di tengah tantangan sosial-ekonomi akibat pandemi COVID-19. Penelitian ini menyoroti kerentanan ekonomi masyarakat pesisir, yang sebagian besar berada pada kelompok berpenghasilan rendah, dengan kondisi yang semakin memburuk akibat pandemi. Meskipun berbagai inisiatif pemerintah, seperti memfasilitasi kerja sama ekspor perikanan, telah diterapkan untuk mendukung penguatan ekonomi lokal, pelaksanaannya masih terkendala oleh keterbatasan layanan administratif dan minimnya partisipasi masyarakat. Hasil penelitian mengungkapkan bahwa program bantuan keuangan selama pandemi sering kali tidak tepat sasaran dan kurang efektif dalam mengatasi permasalahan utama nelayan. Untuk mengatasi tantangan ini, strategi pemberdayaan yang diusulkan mencakup pembentukan koperasi nelayan, pengelolaan usaha secara kolektif, serta penguatan kerja sama dengan pemangku kepentingan. Di Kecamatan Samatiga, upaya pemberdayaan difokuskan pada peningkatan nilai jual hasil tangkapan nelayan melalui kelompok nelayan yang terorganisasi. Namun, keterbatasan struktural dan kendala pemerintah daerah menjadi tantangan dalam keberhasilan program-program tersebut. Pendekatan yang holistik, partisipatif, dan berkelanjutan sangat diperlukan untuk meningkatkan kesejahteraan masyarakat nelayan dan mendorong pengembangan ekonomi lokal yang kokoh di Kabupaten Aceh Barat.